ANALYSIS OF THE EFFECTIVENESS OF THE DUOLINGO APPLICATION IN ENGLISH PRONUNCIATION LEARNING - Rahma Widi; Annisa Tasyakurna M; Hafni Hafsah (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2025)
This research aimed to analyze the effectiveness of using the Duolingo application in learning English pronunciation. This was descriptive qualitative research. The participants consisted of 24 undergraduate students at Institut Az Zuhra. Interviews and observations were conducted to collect data. They were chosen due to lacking at pronouncing the words. It was because they did not get activity about pronunciation when they were in school. After conducting the research, it was found that the Duolingo application used in pronunciation class was effective to be applied. It was fun, enjoyable, interesting, and motivating for the students. It improved their confidence and reduced their pronunciation anxiety. Additionally, there are some limitations of using the Duolingo application, such as annoying advertisements, and it cannot be accessed offline.